2017
DOI: 10.3892/ijmm.2017.3196
|View full text |Cite
|
Sign up to set email alerts
|

CCDC134 serves a crucial role in embryonic development

Abstract: Coiled-coil domain containing 134 (CCDC134), a characterized secreted protein, may serve as an immune cytokine and illustrates its potent antitumor effects by augmenting CD8+ T-cell-mediated immunity. Additionally, CCDC134 may also act as a novel regulator of human alteration/deficiency in activation 2a, and be involved in the p300-CBP-associated factor complex and affect its acetyltransferase activity. To clarify the biological and pathological function of CCDC134, the present study generated a viable and fer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 34 publications
0
19
0
1
Order By: Relevance
“…Recently, it has been shown that Ccdc134 is critical for mouse embryonic development . Ccdc134 −/− mice were non‐viable, with a lethality between E12.5 and E14.5, presumably related to anemia.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been shown that Ccdc134 is critical for mouse embryonic development . Ccdc134 −/− mice were non‐viable, with a lethality between E12.5 and E14.5, presumably related to anemia.…”
Section: Discussionmentioning
confidence: 99%
“…Two members of the γ c cytokine family effectively block CCDC134 binding to activated CD8 + T cells. This provides evidence that CCDC134 may be a potential member of the γ c cytokine family ( 31 ).…”
Section: Discussionmentioning
confidence: 82%
“…Our previous study showed that hemorrhages occur in the brain ventricular space and neural tube, resulting in severe overall brain disorganization and embryonic lethality from embryonic day 12.5 to birth in homozygous Ccdc134 knockout mouse embryos, but not in littermates. 14 In the present study, immunostaining using a specific anti-CCDC134 antibody was performed on sections of human cerebellar autopsy specimens and frozen cerebellar sections from wild-type mice at embryonic, adolescent and adult stages. We found that the CCDC134 protein was highly expressed in the PCs soma.…”
Section: Discussionmentioning
confidence: 99%
“…Intriguingly, Ccdc134 loss leads to severe hemorrhages in the brain ventricular space and neural tube. 14 Thus, we hypothesize that CCDC134 might be critical for brain development.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation